2006
DOI: 10.1111/j.1572-0241.2006.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgical Versus Percutaneous Drainage of Abdominal and Pelvic Abscesses in Crohn's Disease

Abstract: Time to resolution of abdominal or pelvic abscesses in Crohn's disease is similar with percutaneous drainage and surgery. One-third of patients treated with percutaneous drainage required surgery within 1 yr. Earlier intervention for abdominal and pelvic abscesses is associated with shorter time to resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
8

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 6 publications
6
67
1
8
Order By: Relevance
“…If necessary, drainage can be followed by one-stage surgery (resection and anastomosis performed in the same procedure). This approach is especially useful when the abscess develops against a background of active disease [26,43].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…If necessary, drainage can be followed by one-stage surgery (resection and anastomosis performed in the same procedure). This approach is especially useful when the abscess develops against a background of active disease [26,43].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…In another study, 6 of 7 patients that did not have elective surgery had a severe recurrence within 3 years [1] . On the other hand, some studies have shown the majority of patients do well after PAD without definitive surgery and that the recurrence rate is acceptably low [10] . Golfieri et al [8] found that only 12.6% of 70 patients developed a recurrent abscess after a mean follow-up of 39 mo and that only 5/11 of these patients required urgent surgery.…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…A palpable mass is present EDITORIAL in about 1/3 of patients. Rebound tenderness occurs 30% of the time [10] . Clinicians should be aware that elderly or immune suppressed patients sometimes manifest fewer signs and symptoms [9] .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations